Penyelesaian Sengketa Tanah Adat Dalam Perspektif Kearifan Lokal Pada Masyarakat Ngadhu-Bhaga, Kabupaten Ngada-NTT - Elroswit.E.Teresa Gae Soro; Bernadio Marsico Oematan; Mariani Indriani Jesika Jawa; Claudia Hironima Letik; Michael A.Siki; Servasius S. Sunardi; Stefanus Don Rede (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this study is to develop dispute resolution options from the perspective of local wisdom in the Ngadhu-bhaga community, Flores, East Nusa Tenggara. In socio-cultural reality, local wisdom is plural. The diversity of local wisdom is based on the cosmology of the local community. Conflict resolution is always directed at harmonious efforts. So, the resolution of customary land disputes from the perspective of local wisdom in the Ngadhu-Bhaga community is oriented towards this perspective.